The Informer Based on a Novel by Liam O'Flaherty - Knox, Garth; O'Flaherty, Liam (BFI, 2017)
Based on Liam O’Flaherty’s popular novel this gripping thriller is set amongst a group of revolutionaries in the newly independent Ireland of 1922. When one of their number, Francis, kills the chief of police he goes on a run. But when he returns to say goodbyes to his mother and former lover he is cruelly betrayed by his onetime friend, Gypo. Newly restored by the BFI National Archive, with a new score from acclaimed violist/composer Garth Knox and premiered at the 2016 BFI London Film Festival, "The Informer" is one of the finest British films of the 1920s and deserves a place alongside other silent greats such as "Blackmail", "A Cottage on Dartmoor" and "Piccadilly". This Dual Format Edition includes the silent version alongside the rare sound version produced at the same time. [www.bfi.org.uk]